Feasibility of endoscopic evaluation of Helicobacter pylori infection status by using the Kyoto classification of gastritis in the population‐based gastric cancer screening program: A prospective cohort study. Issue 3 (14th July 2021) - Hirai, Ryosuke; Hirai, Mami; Shimodate, Yuichi; Minami, Mariko; Ishikawa, Sho; Kanadani, Takafumi; Takezawa, Rio; Doi, Akira; Nishimura, Naoyuki; Mouri, Hirokazu; Matsueda, Kazuhiro; Yamamoto, Hiroshi; et al.
Abstract: Background and aims: We have started a new population‐based endoscopic gastric cancer screening program in Kurashiki city with consideration of Helicobacter pylori infection status based on endoscopic features. We aimed to verify the feasibility of this attempt in a prospective case‐registration study (UMIN000028629). Methods: Data were collected from 1784 subjects without past eradication of H. pylori and who underwent endoscopic gastric cancer screening in Kurashiki Central Hospital Preventive Healthcare Plaza from September 2017 to June 2018. Endoscopic judgment of H. pylori infection status was made according to the Kyoto classification of gastritis. For comparison, a combination serum test of anti‐ H. pylori antibody and pepsinogen I and II, the ABC method, was used. Results: The endoscopic diagnoses were nongastritis, 1215 (68.1%); active or inactive gastritis, 469 (26.3%); and undefined, 23 (1.3%). With the ABC method as a reference standard, the false‐negative rate of the endoscopic judgment for H. pylori infection was 16.3% (95% confidence interval: 13.1%‐20.0%). Most false‐negative cases were of Group B in the ABC method, which is considered gastritis with mild mucosal atrophy. Antibody titers in this population were mostly in the weak‐positive range but clinically significant elevation of the antibody suggesting current infection was observed in some cases. Conclusions: Endoscopic diagnosis of H. pylori infection status in a population‐based gastric cancer screening program is mostly reliable, but false‐negative results may occur, especially in patients with mild gastric atrophy. To avoid this limitation, we recommend adding H. pylori antibody test to the program.